2002
DOI: 10.1080/00223980209604134
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological Beliefs and Thinking About Everyday Controversial Issues

Abstract: The authors investigated the relationship between individuals' beliefs about the nature of knowledge and the nature of learning (epistemological beliefs) and their thinking about everyday controversial issues. Adults (N = 174) ranging in age from 17 to 71 years old with a mean age of 38 completed the Schommer Epistemological Questionnaire (M. Schommer, 1990), which assessed their beliefs in the certainty and organization of knowledge and the speed and control of learning. After they had completed the questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 20 publications
5
67
1
11
Order By: Relevance
“…There are some researches in line with the result of this study, but also some other researches do not support it. The previous researches revealed that the beliefs of students on one truth had close relation with achievement motivation (Buehl, 2003) performance objectives focusing on extrinsic motivation (Cavallo et al, 2004;Paulsen & Feldman, 2005), and negative correlation with self-efficacy which is the predictor of extrinsic motivation (Schommer & Aikins, 2002). However, there are also some researches results contrary to the findings of this study.…”
Section: Discussion Conclusion and Recommendationscontrasting
confidence: 86%
“…There are some researches in line with the result of this study, but also some other researches do not support it. The previous researches revealed that the beliefs of students on one truth had close relation with achievement motivation (Buehl, 2003) performance objectives focusing on extrinsic motivation (Cavallo et al, 2004;Paulsen & Feldman, 2005), and negative correlation with self-efficacy which is the predictor of extrinsic motivation (Schommer & Aikins, 2002). However, there are also some researches results contrary to the findings of this study.…”
Section: Discussion Conclusion and Recommendationscontrasting
confidence: 86%
“…The theoretical lens of Schommer's (1990) perspective posits four dimensions of epistemological beliefs, ranging from naïve to sophisticated: (a) structure of knowledge (ranging from isolated bits to integrated concepts), (b) stability of knowledge (ranging from certain to evolving), (c) speed of learning (from quick or not at all to gradual), and (d) ability to learn (ranging from fixed at birth to improvable) (Schommer, 1994a(Schommer, , 1994bSchommer-Aikins & Hutter, 2002). The Epistemological Questionnaire, developed by Schommer, has also provided evidence attesting to the multidimensionality of epistemological beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research investigations indicate mixed results and suggest the need to examine further the dimensionality of personal epistemological beliefs. The work of Phillips, Schommer, and others (Phillips, 2001;Schommer, 1990Schommer, , 1993Schommer, Crouse & Rhodes, 1992; Aikins, Duell & Hutter, 2005;Schommer-Aikins & Hutter, 2002) shows that there are four distinct dimensions of personal epistemology. However, other research studies criticising the use of a priori subsets in factor analysis (Bråten & Strømsø, 2005) have found at an itembased level of analysis, that three (Cano, 2005;Qian & Alverman, 1995) to five (Schraw, Bendixen & Dunkle, 2002) dimensions of epistemology are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Because critical thinking seems to be intertwined with epistemological beliefs (Hyytinen et al 2014;Schommer-Aikins & Hutter, 2002), we first discuss the results of the quality of the critical thinking skills of our sample of applicants for entry to a university faculty of educational sciences in light of the Reflective Judgment Model (King & Kitchener, 1994) and other previous studies on the epistemological aspects of critical thinking. Typically, college students' epistemic beliefs can be located on the quasi-reflective level, in which multiple viewpoints and information related to ill-defined problems are recognized (King & Kitchener, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the more education adults have received, the more probable it is that they will perceive knowledge as complex and constantly in flux (Schommer, 1998). Further, this belief in the complexity and perpetual transformation of knowledge increases the individual's willingness to take multiple perspectives and alter their thinking (Schommer-Aikins & Hutter, 2002). In brief, well-developed epistemic beliefs are related to important elements of critical thinking, namely to the ability to see alternative viewpoints and to reflect on one's own thinking.…”
Section: Interconnections Of Critical Thinking and Epistemic Beliefsmentioning
confidence: 99%